Extraocular Muscle Cysticercosis Masquerading Idiopathic Orbital Inflammatory Syndrome(IOIS) - Meenu Babber; Shikha Baisakhiya; Prafulla Manjhi; Neha Sharma; Nipun Chopra (Delhi Journal of Ophthalmology)
Intraocular infection by Cysticercus cellulosae larva are often found as part of a generalized systemic infestation. Reports of orbital adnexal cysticercosis are uncommon, despite the high incidence of brain and ocular involvement. With isolated infestation of extraocular muscle being exceedingly rare, we at our institute report a rare case of isolated right inferior rectus muscle cysticercosis which presented with unilateral eccentric proptosis and restriction of upgaze